Mitigation of Global Cooling by Stratospheric Chemistry Feedbacks in a Simulation of the Last Glacial Maximum. Issue 17 (12th September 2018) - Noda, Satoshi; Kodera, Kunihiko; Adachi, Yukimasa; Deushi, Makoto; Kitoh, Akio; Mizuta, Ryo; Murakami, Shigenori; Yoshida, Kohei; Yoden, Shigeo
Abstract: The impact of changes in the stratospheric ozone profile in the Last Glacial Maximum simulation under reduced atmospheric CO2 concentrations and different orbital elements is investigated using an Earth System Model. For this, simulations including an interactive atmospheric chemistry scheme is compared with simulations using the prescribed ozone profile for a preindustrial control run of the fifth Coupled Model Intercomparison Project (CMIP5). The contribution of the interactive chemistry reveals a significant warming of zonal mean surface temperature, +0.5 K (approximately 20%) in the tropics and up to +1.6 K in high latitudes. In the tropics, this mitigation of global cooling is related to longwave radiative feedbacks associated with circulation‐driven increases in the lower stratospheric ozone and in the stratospheric water vapor, and related decrease in cirrus clouds. The mechanisms are of opposite sign to and consistent with those obtained by increased CO2 simulations. In high latitude, the stronger mitigation of cooling is associated with sea ice retreat, which has the same sign to and is consistent with our previous paleoclimate simulation of the mid‐Holocene (CO2 concentration of 280 ppm and orbital element change) including interactive chemistry. Most previous Last Glacial Maximum simulations with the prescribed ozone profile exhibited cold bias in the tropics compared with geological proxy data, whereas this bias is reduced in our simulations through the use of the interactive ozone chemistry, although a warmer bias in the midlatitude is enhanced. We recommend climate models to include ozone profiles that are consistent with CO2 concentrations and solar forcing. Key Points: Including ozone chemistry feedbacks mitigates global cooling in a paleoclimate simulation under reduced CO2 and different orbital elements This is due to ozone and related water vapor and cirrus cloud feedbacks, consistent with results of a previous study under increased CO2 Including ozone feedbacks brings our model results closer to the expectation value of geological proxy estimates